Aging-induced changes in 24-h rhythms of mitogenic responses, lymphocyte subset populations and neurotransmitter and amino acid content in rat submaxillary lymph nodes during Freund's adjuvant arthritis - Garcia Bonacho, M. (2001)
In young (two months) and aged (18 months) male rats injected s.c. with Freund´s adjuvant or adjuvant´s vehicle 18 days earlier, 24-h variations in mitogenic responses, lymphocyte subsets and monoamine and amino acid content were examined in submaxillary lymph nodes. Mitogenic responses to concanavalin A (Con A) and lipopolysaccharide (LPS) were higher during the light phase of daily photoperiod. Old rats exhibited a suppressed or impaired mitogenic response to Con A but not to LPS. Acrophases of 24-h rhythm in lymphocyte subset populations in submaxillary lymph nodes were: 18:37-19:44h (B cells), 09:00-10:08h (T and CD4(+) cells) and 12:19-15:58h (CD8(+) cells). Aging augmented B cells and decreased T, CD4(+) and CD8(+) cells. Significant correlations were found between Con A activity and T cells, between lymph node 5HT content and B, T and CD8(+) lymphocytes, and between lymph node 5HT and taurine and GABA content. Aging increased lymph node 5HT content but did not modify NE content. Lymph node concentration of aspartate, glutamate and taurine was higher at night while that of GABA attained peak values at late afternoon. Old rats injected with Freund´s adjuvant showed a higher mean value (glutamate) and smaller amplitude (glutamate, taurine) than their respective young controls. The results further document the effects of aging on the chronobiology of the immune system.